RETRACTED: Methodological aspects of internal control of the enterprise management system - Zakirova Alsou; Klychova Guzaliya; Valiev Ayrat; Khusainov Shaukat; Ullah Raheem; Sagadeeva Elza (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001